High and Sustained Participation in a Multi-year Voluntary Performance Measurement Initiative Among Primary Care Teams - Carol Mulder; Jennifer Rayner (Kerman University of Medical Sciences, 2022)
BackgroundThe province of Ontario, Canada has made major investments in interdisciplinary primary care teams. There is interest in both demonstrating and improving the quality of care they provide. Challenges include lack of consensus on the definition of quality and evidence that the process of measuring quality can be counter-productive to actually achieving it. This study describes how primary care teams in Ontario voluntarily measured quality at the team level. MethodsData for this 4-year observational study came from electronic medical records (EMRs), patient surveys and administrative reports. Descriptive statistics were calculated for individual measures (eg, access, preventive interventions) and composite indicators of quality and healthcare system costs. Repeated measures identified patient and practice characteristics related to quality and cost outcomes. ResultsTeams participated in an average of 5 of 8 possible iterations of the reporting process. There was variation between teams. For example, cervical cancer screening rates ranged from 21 to 86% of eligible patients. Rural teams had significantly better performance on some indicators (eg, continuity) and worse on others (eg, cancer screening). There were some statistical but small changes in performance over time. ConclusionHigh, sustained voluntary participation suggests that the initiative served a need for the primary care teams involved. The absence of robust data standards suggests that these standards were not crucial to achieve participation. The constant level of performance might mean that measurement has not yet led to improvement or that measures used might not accurately reflect improvement. The data reinforce the need to consider differences between rural and urban settings. They also suggest that further analysis is needed to identify characteristics that teams can change to improve the quality of care their patients experience. The study describes a practical, sustainable real-world approach to performance measurement in primary care that was attractive to interdisciplinary teams.